2015
DOI: 10.2147/copd.s73751
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body vibration improves functional capacity and quality of life in patients with severe chronic obstructive pulmonary disease (COPD): a pilot study

Abstract: BackgroundExercise intolerance is a common development in patients with chronic obstructive pulmonary disease (COPD). There is little data on the use of an isolated program using vibration platform training on functional capacity in these patients, which is an area that deserves investigation.AimTo investigate the effect of training on a vibrating platform (whole-body vibration [WBV]) on functional performance and quality of life of subjects with COPD.MethodsA randomized controlled crossover pilot study with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Some associated physiotherapy strategies such as respiratory muscle training can produce beneficial effects in COPD subjects (Beaumont et al, 2015;Neves et al, 2014). Another strategy that has gained strength and has been associated with improvement in skeletal muscle, especially the lower limbs, and functional capacity in COPD subjects is whole body vibration, making it a potential means to recover lean mass (Braz Júnior et al, 2015;Cardim, Marinho, Nascimento, Fuzari, & Dornelas de Andrade, 2016;Sá-Caputo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Some associated physiotherapy strategies such as respiratory muscle training can produce beneficial effects in COPD subjects (Beaumont et al, 2015;Neves et al, 2014). Another strategy that has gained strength and has been associated with improvement in skeletal muscle, especially the lower limbs, and functional capacity in COPD subjects is whole body vibration, making it a potential means to recover lean mass (Braz Júnior et al, 2015;Cardim, Marinho, Nascimento, Fuzari, & Dornelas de Andrade, 2016;Sá-Caputo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our study has shown that patients are at least able to maintain their exercise performance in the context of the 3 months exercise training which can be seen as an important benefit in patients with COPD. However, in another recent study with a small sample size WBVT improved functional capacity in the 6-MWT of patients with COPD undergoing a training program on the vibrating platform as well as in all domains of the SGRQ quality of life in a safe and feasible way [30]. …”
Section: Discussionmentioning
confidence: 99%
“…At this level of evidence, WBV improved functional performance of the lower limbs [ 22 , 24 , 25 ] and QoL [ 22 ] of people with COPD (see Table 4 ). Two studies met the ISMNI recommendations [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The descriptions and level of evidences of six reviewed studies are shown in Table 3 . The level of evidence was Level II [ 23 , 26 , 27 ] and Level III-1 [ 22 , 24 , 25 ]. The degree to which the six reviewed papers met ISMNI recommendations is shown in Table 4 .…”
Section: Resultsmentioning
confidence: 99%